Évaluer des compétences : de l'intention des enseignants au vécu des étudiants. Le cas d'un atelier d'improvisation - Catherine Archieri
This article presents the results of a scientific investigation into the way in which a training course devoted to the development of improvisation skills can be evaluated without taking into account the quality of the improvisation (the aim is not to train actors but STAPS students) but rather the commitment to a process of letting go and taking others into account, as recommended in improvisation. The research question is: What relationships exist between teacher intentions and student experiences with assessment? The hypothetical-theoretical approach used to conduct this study has made it possible to uncover regularities, in terms of configuration, whose salient results are that it is possible to evaluate the development of a skill, provided that metacognition and the quality of the psycho-affective relationship between the individuals are prioritized.